The Interactive Multimedia Based on Theo-Centric Approach as Learning Media during the Covid-19 Pandemic - Hazrullah; Azmil Hasan Lubis (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
In online learning situation learning media will have an impact on increasing student motivation in participating in the learning process. This study aims to develop interactive multimedia based on the Theo-centric approach as a proper and practical learning media for elementary school students during the Covid-19 pandemic. This research is research and development. The subjects of this research are media experts, linguists, teachers, and students. Determination of research subjects is done by purposive sampling technique. The research data was obtained by using a questionnaire technique. The analysis technique used is descriptive statistics with the help of a score trend table. The results showed that the product developed was feasible and practical to be used as a learning medium for elementary school students during the Covid-19 pandemic. This can be seen from the results of the feasibility test from media experts and linguists who assessed that the product developed was in the very feasible category. On the other hand, the results of the practicality assessment by teachers and students indicate that the product developed is in the very practical category. Therefore, interactive multimedia based on the Theo-centric approach can be used as a learning media for elementary school students during the Covid-19 pandemic.